Costing - Lucey, T. (Continuum, 2002)
Covering the principles, techniques and methods involved in cost accountancy, this text provides coverage of professional and college syllabuses for cost accountancy. In the first part of the book there is detailed coverage of the objectives, principles, techniques and methods of cost accountancy relating to the analysis and gathering of costs and cost ascertainment. The second part of the book concentrates upon the use of cost information for planning, control and decision making. At each stage, concepts are illustrated by practical examples and placed into context so that the reader is aware of the importance and relationships of the various aspects of costing